Tissue Specific Promoters in Colorectal Cancer. (15th November 2015) - Rama, A. R.; Aguilera, A.; Melguizo, C.; Caba, O.; Prados, J.
Abstract : Colorectal carcinoma is the third most prevalent cancer in the world. In the most advanced stages, the use of chemotherapy induces a poor response and is usually accompanied by other tissue damage. Significant progress based on suicide gene therapy has demonstrated that it may potentiate the classical cytotoxic effects in colorectal cancer. The inconvenience still rests with the targeting and the specificity efficiency. The main target of gene therapy is to achieve an effective vehicle to hand over therapeutic genes safely into specific cells. One possibility is the use of tumor-specific promoters overexpressed in cancers. They could induce a specific expression of therapeutic genes in a given tumor, increasing their localized activity. Several promoters have been assayed into direct suicide genes to cancer cells. This review discusses the current status of specific tumor-promoters and their great potential in colorectal carcinoma treatment.